The Influence of School Principal Leadership and School Organizational Climate on the Performance of Public Elementary School Teachers - Sugiyanto, Sugiyanto; Egar, Ngasbun; Abdullah, Ghufron (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the influence of school principal leadership and school organizational climate on the performance of public elementary school teachers in Singorojo District, Kendal Regency. The research employed a quantitative approach with a correlational design. The population consisted of 268 teachers from 30 public elementary schools, from which 160 respondents were selected using proportional random sampling. Data were collected through a closed-ended questionnaire using a Likert scale and analyzed using descriptive statistics and multiple linear regression techniques. The results showed that both school principal leadership and school organizational climate significantly influence teacher performance, both partially and simultaneously. These findings highlight the importance of strengthening leadership capacity and fostering a positive organizational climate to improve the quality of education in primary schoolsThis study aims to analyze the influence of school principal leadership and school organizational climate on the performance of public elementary school teachers in Singorojo District, Kendal Regency. The research employed a quantitative approach with a correlational design. The population consisted of 268 teachers from 30 public elementary schools, from which 160 respondents were selected using proportional random sampling. Data were collected through a closed-ended questionnaire using a Likert scale and analyzed using descriptive statistics and multiple linear regression techniques. The results showed that both school principal leadership and school organizational climate significantly influence teacher performance, both partially and simultaneously. These findings highlight the importance of strengthening leadership capacity and fostering a positive organizational climate to improve the quality of education in primary schools.